Health Promotion on Adolescent Mental Health at SMKS Kesehatan Husada Pratama Serang City in 2024: Upaya Promosi Kesehatan Terhadap Kesehatan Mental Remaja di SMKS Kesehatan Husada Pratama Kota Serang Tahun 2024 - Peristiowati, Yuli; Bustomi, Sadya; Prihayati (Journal of Community Empowerment for Multidisciplinary (JCEMTY), 2024)
Depression in adolescents can arise due to several things such as academic pressure, bullying, family factors and economic problems. Data in Indonesia shows that suicide cases can reach 10,000 or the equivalent of every day for one hour there is a suicide case. According to a suciodologist 4.2% of adolescents in Indonesia have thought about suicide. Among students 6.9% had suicidal intentions while another 3% were actually involved in suicide attempts. Health promotion aims to improve the ability of the community through learning from by and for the community in accordance with local socio-cultural conditions and supported by health-oriented public policies. The purpose of community service activities is that students are expected to be able to apply the concept of health education in real terms related to adolescent mental health at Husada Pratama Health SMKS in Serang City, so that they can contribute to improving public health status, especially for adolescents. The results of community service activities can be concluded that there is still a lack of knowledge about mental health in students which makes students not understand the importance and impact that will occur if they do not maintain mental health.